Keberhasilan Asi Eklusif Pada Bayi Mempengaruhi Teknik Menyusui Yang Benar Pada Ibu Di Kecamatan Kuranji Padang Tahun 2023 - Eka Seba Marta (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2023)
The coverage of exclusive breastfeeding in infants 0-6 months is 42%. The importance of knowing the correct breastfeeding technique greatly affects the success of exclusive breastfeeding in infants. The research objective was to determine the success of exclusive breastfeeding for infants in the Kuranji sub-district in 2023. This type of research was analytic with a cross-sectional design. The population is breastfeeding mothers who have babies 6-12 months, totaling 119 people. Purposive sampling technique, amounting to 54 respondents. Chi-square analysis 95% CI (α = 0.05). The research was conducted on 02 May – 25 August 2023.